Mineralogical and geochemical characteristics of rare earth mineralisation in the Middle Dnipro region (on the example of the Kotlyarivka ore occurence) - V. V. Sukach; L. V. Isakov; Yu. Ye. Khomych (Мінеральні ресурси України)
The article presents a mineralogical, petrographic, and geochemical characterization of the rare earth mineralization of the Kotlyarivka ore occurrence, which was discovered by drill hole 114 in the south-western part of the Krynychky plagiogranite-migmatite dome during geological exploration of the southern part of the Verkhivtseve greenstone structure and its granitoid framing. Rare earth elements (REE) are critically important minerals for many countries, including EU, USA, Canada, and Australia, and other developed countries. The Ukrainian Shield is one of the largest REE metallogenic provinces in Europe. In particular, the Middle Dnipro megablock is a prospective but under-explored region for the discovery of new REE deposits. Its prospects are associated with subalkaline and alkaline Mesoarchaean granitoids and metasomatites of the Tokivske, Mokra Moskovka, and Demuryno complexes. Comprehensive studies of core samples from primary and weathered rocks of the Kotlyarivka occurrence have revealed that monazite is the mine mineral concentrator of REE and yttrium. It was determined that monazite underwent two main stages of alterations: endogenic hydrothermal-metasomatic and hypergenic associated with weathering crust formation. Other minerals, such as apatite, zircon, and leucoxene, also contain lanthanides and yttrium. The findings highlight the critical need for the development of the mineral resource base for REE, involving the re-evaluation of known deposits and the search for new ones. This usually requires scientific support and modern laboratory equipment to accurately determine the composition and genetic features of productive mineralization. Despite some challenges, such as the limited number of samples available for study, the research provided new important data that contributed to the understanding rare earth elements mineralization in the studied Kotlyarivka occurrence and the Middle Dnipro region as a whole. Continuing such studies and conducting comprehensive full-scale research on REE mineralization in the Central Dnipro region will yield high theoretical and practical results.